2017
DOI: 10.1155/2017/3521541
|View full text |Cite
|
Sign up to set email alerts
|

ANA-Negative Hydralazine-Induced Pericardial Effusion

Abstract: This case describes a patient with pericardial effusion as a phenomenon of the drug-induced lupus erythematosus (DILE) syndrome due to hydralazine. The relevance of this case report lies in the fact that although hydralazine has been a known causative agent of DILE, its presentation may involve a negative anti-nuclear antibody (ANA) study. Pericardial effusion is a documented adverse effect as a result of hydralazine use. It is typically common to screen for DILE with the serum ANA test prior to proceeding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…HILS should be suspected in any patient on hydralazine presenting with unexplained effusion; moreover, in our patient, additional laboratory evidence revealed the presence of active lupus, including low C3, elevated ESR and CRP, pancytopenia, negative anti-dsDNA, and positive anti-histone antibody ( 5 ). We believe the clinical picture and laboratory findings of our patient were consistent with the presentation of HILS with negative ANA ( 3 , 4 ).…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…HILS should be suspected in any patient on hydralazine presenting with unexplained effusion; moreover, in our patient, additional laboratory evidence revealed the presence of active lupus, including low C3, elevated ESR and CRP, pancytopenia, negative anti-dsDNA, and positive anti-histone antibody ( 5 ). We believe the clinical picture and laboratory findings of our patient were consistent with the presentation of HILS with negative ANA ( 3 , 4 ).…”
Section: Introductionsupporting
confidence: 81%
“…Infrequently, serositis leading to pericardial and pleural effusions can develop. Several case reports have described HILS presenting with pericarditis and/or cardiac tamponade ( 1 4 ). Following the African American Heart Failure trials that demonstrated the mortality benefit of BiDil (combination of hydralazine and isosorbide dinitrate), hydralazine is more frequently prescribed than ever before ( 7 , 9 ), and the incidences of HILS are likely to rise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations